Dear Dr. Bell-- your friend, Helen Keller - St. George, Judith, 1931- (Putnam's Sons, 1992)
Follows the parallel lives of Helen Keller and Alexander Graham Bell, who continued to encounter and support each other from that eventful meeting when he recommended she be given a teacher and thus led her to Annie Sullivan.